Accurate and safe diagnosis and treatment of neoplastic biliary lesions using a novel 9F and 11F digital single-operator cholangioscope - Robles-Medranda, Carlos; Alcivar-Vasquez, Juan; Raijman, Isaac; Kahaleh, Michel; Puga-Tejada, Miguel; Del Valle, Raquel; Alvarado, Haydee; Cifuentes-Gordillo, Carlos; Binmoeller, Kenneth F.; Baptista, Alberto Jose; Barreto-Perez, Jonathan; Rodriguez, Jorge; Egas-Izquierdo, Maria; Cunto, Domenica; Calle-Loffredo, Daniel; Lukashok, Hannah; Baquerizo-Burgos, Jorge; Tabacelia, Daniela (Endoscopy International Open, 2024)
Background and study aims Digital single-operator cholangioscopy (DSOC) allows the diagnosis of biliary duct disorders and treatment for complicated stones. However, these technologies have limitations such as the size of the probe and working channel, excessive cost, and low image resolution. Recently, a novel DSOC system (eyeMAX, Micro-Tech, Nanjing, China) was developed to address these limitations. We aimed to evaluate the usefulness and safety of a novel 9F and 11F DSOC system in terms of neoplastic diagnostic accuracy based on visual examination, ability to evaluate tumor extension and to achieve complete biliary stone clearance, and procedure-related adverse events (AEs).Patients and methods Data from ≥ 18-year-old patients who underwent DSOC from July 2021 to April 2022 were retrospectively recovered and divided into a diagnostic and a therapeutic cohort.Results A total of 80 patients were included. In the diagnostic cohort (n = 49/80), neovascularity was identified in 26 of 49 patients (46.9%). Biopsy was performed in 65.3% patients with adequate tissue sample obtained in 96.8% of cases. Biopsy confirmed neoplasia in 23 of 32 cases. DSOC visual impression achieved 91.6% sensitivity and 87.5% specificity in diagnosing neoplasms. In the therapeutic cohort (n = 43/80), 26 of 43 patients required lithotripsy alone. Total stone removal was achieved in 71% patients in the first session. Neither early nor late AEs were documented in either the diagnostic or therapeutic cohort.Conclusions The novel DSOC device has excellent diagnostic accuracy in distinguishing neoplastic biliary lesions as well as therapeutic benefits in the context of total stone removal, with no documented AEs.
Keywords: Cholangioscopy; Strictures; Pancreatobiliary (ERCP/PTCD); Stones; Tissue diagnosis